A 38,000-dalton membrane protein (p38) present in synaptic vesicles. - Jahn, R (1985)
A protein with an apparent molecular mass of 38,000 daltons designated p38 was found in synaptic vesicles from rat brain. The subcellular distribution of p38 and some of its properties were determined with the aid of polyclonal and monoclonal antibodies. The subcellular distribution of p38 was similar to that of synapsin I, a synaptic-vesicle specific phosphoprotein. p38 in the synaptic vesicle fraction purified by controlled-pore glass bead chromatography showed an enrichment of more than 20-fold over the crude homogenate. Immunostaining of sections through various brain regions revealed an intense labeling of most, and possibly all, nerve terminals. Only faint reaction in the region of the Golgi apparatus and no detectable labeling of axons and dendrites was observed. Two-dimensional electrophoresis revealed that p38 has an acidic pI. Solubilization experiments, as well as phase separation experiments using Triton X-114, indicated that p38 is an integral membrane protein. Binding of antibodies to intact synaptic vesicles, as well as controlled proteolytic digestion of intact and detergent-treated vesicles, revealed that p38 has a domain exposed on the cytoplasmic surface.